Macro Framework Design for Policies on Developing and Expanding Employment Opportunities for Higher Education Graduates in the Country - Shokri, Malek; Beikzad, Jafar; Islambolchi, Alireza; Gharehdaghi, Rostam; Hamidi, Kambiz (International Journal of Innovation Management and Organizational Behavior (IJIMOB), 2024)
Objective: The purpose of the present study is to design and propose a macro framework for policies aimed at developing and expanding employment opportunities for higher education graduates in the country. Methodology: The research approach is qualitative, utilizing thematic analysis. Data were collected through semi-structured interviews with a group of experts. The expert group members were selected using purposeful sampling from three categories: university faculty members (7 individuals), managers related to national-level institutions involved in policymaking and law enforcement related to employment (3 individuals), and mid-level managers working at provincial levels in institutions related to employment (4 individuals). The information obtained from the interviews with 14 experts was used to form the theoretical modeling. During the completion phases of the research, the opinions of 4 additional experts (with educational backgrounds in administrative sciences) were also utilized to ensure theoretical saturation and achieve an acceptable level of validity and reliability of the findings. Data were processed and reviewed in multiple stages, and after ensuring acceptable validity and reliability for the qualitative model, they were summarized and presented in the form of a theoretical policy development and expansion model for employment opportunities for higher education graduates in the country. Findings: The model includes 3 comprehensive macro frameworks (policies to strengthen the demand side in the employment equation, policies to strengthen the supply side in the employment equation, and dual employment creation policies), 13 organizing themes, and 56 basic themes. Conclusion: Based on the findings and results, research proposals are presented to guide the selection of policies for developing and expanding employment opportunities for higher education graduates in the country.